Post-partum streptococcal toxic shock syndrome associated with necrotizing fasciitis - Wei, Chuan Chua; Mazlan, Mohd Zulfakar; Ali, Saedah; Che Omar, Sanihah; Wan Hassan, Wan Mohd Nazaruddin; Seevaunnantum, S. Praveena; Mohd Zaini, Rhendra Hardy; Hassan, Mohd Hasyizan; Muhd Besari, Alwi; Abd Rahman, Zaidah; Ayub, Zeti Norfidiyati Salmuna; Abd Ghani, Sabrina; et al. (Elsevier, 2017)
We report a fatal case of post-partum streptococcal toxic shock syndrome in a patient who was previously healthy and had presented to the emergency department with an extensive blistering ecchymotic lesions over her right buttock and thigh associated with severe pain. The pregnancy had been uncomplicated, and the mode of delivery had been spontaneous vaginal delivery with an episiotomy. She was found to have septicemic shock requiring high inotropic support. Subsequently, she was treated for necrotizing fasciitis, complicated by septicemic shock and multiple organ failures. A consensus was reached for extensive wound debridement to remove the source of infection; however, this approach was abandoned due to the patient’s hemodynamic instability and the extremely high risks of surgery. Both the high vaginal swab and blister fluid culture revealed Group A beta hemolytic streptococcus infection. Intravenous carbapenem in combination with clindamycin was given. Other strategies attempted for streptococcal toxic removal included continuous veno-venous hemofiltration and administration of intravenous immunoglobulin. Unfortunately, the patient’s condition worsened, and she succumbed to death on day 7 of hospitalization.